Karakteristik Sensoris Snack Bars dari Tepung Komposit Pisang Goroho (Musa acuminate, L), Kedelai (Glycine max) dan Kenari (Canarium indicum L.) - Cinka W. Siahaan; Erny J. N. Nurali; Jenny E. A. Kandou (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2022)
The purpose of this study was to evaluate the sensory characteristics of snack bars from composite of goroho plantain flour, soybean and canary. This study used a completely randomized design (CRD) method consisting of 5 (five) treatments and 3 (three) replications with the following treatments : treatment A 40 g of goroho plantain flour, 35 g of soybean flour, 25 g of canary, treatment B 50 g of goroho plantain flour, 30 g of soybean flour and 20 g of canary, treatment C 60 g of goroho plantain flour, 25 g of soybean flour and 15 g of canary, treatment D 70 g of goroho plantain flour, 20 g of soybean flour and 10 g of canary and treatment E 80 g of goroho plantain flour, 15 g of soybean flour and 5 g of canary. The result interm of color: neutral – slightly like, aroma:  neutral – slightly like, taste: neutral – slightly like and texture: neutral – slightly like. Keywords : snack bars, composite flour, goroho plantain, soybean, canary